Mietwagenunternehmen an europäischen Flughäfen. Ergebnisse einer Zufriedenheitsanalyse. - Dieleman, Owen; Rosskopf, Iris; Trausch, Zoé (DVV Media Group, 2009)
Die Sicherstellung der landseitigen Erreichbarkeit ist eine wesentliche Voraussetzung, um als Flughafen bei der dynamischen Entwicklung des Luftverkehrs wettbewerbsfähig zu bleiben. Mietwagenunternehmen leisten ebenfalls einen Beitrag zur landseitigen Anbindung von Flughäfen, sind jedoch bisher kein Schwerpunkt der üblichen Verkehrsplanung. Um Kenntnisse über die Situation und die Zufriedenheit von Mietwagenunternehmen an europäischen Flughäfen zu gewinnen, wurde von der ZIV GmbH eine Befragung durchgeführt.

Managing car hire companies, and accessing their check-in counters, at airports has so far not been given much attention with regard to transport related matters. Improving links with public transport, plus access to car parking for individual travelers, appear to be the focus of attention. These factors have given the impetus for a survey of airport-based car hire firms. The location of car hire companies' reservation and check-in counters, their accessibility, signs pointing to their location, and easy recognition, are immensely important. In the case of counters located in airport terminals, all these factors have been awarded marks yet not so with regard to signs giving directions or actually picking-up a hired car. Car hire firms' operational sequence seems adversely affected by transport- related problems in more than two thirds of all cases, as well as by a lack of adequate space for returning hired cars and parking. With regard to collaboration with an airport's management, the majority of the carhire firms investigated expressed the wish to see more consideration given to their requirements, to be more involved in future panning and enjoy better communication.
Car hire companies at Europe's airports.
Keywords: Verkehr; Luftverkehr; Straßenverkehr; Flughafen; Erreichbarkeit; Befragung; Wettbewerb; Dienstleistung; Vermietung; Kraftfahrzeug; Mietwagen; Autovermietung; Wettbewerbsfähigkeit